2007
DOI: 10.1007/s10484-007-9045-7
|View full text |Cite
|
Sign up to set email alerts
|

Headache Treatment with Pulsing Electromagnetic Fields: A Literature Review

Abstract: Pulsing electromagnetic field (PEMF) therapy may be a viable form of complementary and alternative medicine. Clinical applications include the treatment of fractures, wounds, and heart disease. More recent applications involve treatment of recurrent headache disorders. This paper reviews available studies investigating PEMF for headache management. Possible mechanisms for effects (neurochemical, electrophysical, and cardiovascular) are discussed. The available data suggest that PEMF treatment for headache meri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
0
7
0
1
Order By: Relevance
“…The current study has several strengths in comparison with the previous studies that were collected by Vincent et al in. 17 For example, the existence of the parallel placebo group in a randomized clinical trial, assessment of PEMF in RM patients for whom the routine treatment did not work, and consideration of menstrual relation to migraine as factors in a mixed model analysis have not been previously included in published work.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The current study has several strengths in comparison with the previous studies that were collected by Vincent et al in. 17 For example, the existence of the parallel placebo group in a randomized clinical trial, assessment of PEMF in RM patients for whom the routine treatment did not work, and consideration of menstrual relation to migraine as factors in a mixed model analysis have not been previously included in published work.…”
Section: Discussionmentioning
confidence: 99%
“…25,33,34 Many of the studies from 1985 to 2005, gathered in a review article, illustrated the effect of the use of large spread spectrum of PEMF doses on decreasing headache activity. 17 Although most of these research studies had no control or comparison group, or had very brief follow-up periods and uncompleted reports of dosimeter. Sherman et al in 1998 revealed a therapeutic effect of PEMF at 27.12 MHz in their pilot study of six migraine patients exposed to a PEMF machine, showing a change in headache activity from 3.32 to 0.58 per week compared to the controls.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations